Pengembangan Media Basuka (Baut Susun Matematika) untuk Meningkatkan Hasil Belajar pada Pembelajaran Matematika Siswa Kelas IV SDN 5 Rasau Jaya - Devi Devi (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
Development of Basuka Media on Mathematics Learning for Grade IV Students of SDN 5 Rasau Jaya. This study aims to develop Basuka media towards the interest in learning broad material of flat building class IV SDN 5 Rasau Jaya. This research method uses Research and Development (R&D). While the research model used, namely the development model of Borg and Gall.Data collection techniques using questionnaires and tests. The results showed that there was a significant difference in students' learning interest in flat building material after the development of Basuka media. This is shown by the pre-test result of 45. Based on the result of obtaining a post-test score of 96 is better than the result of the pre-test score, at the specified KKM which is 70. Basuka media feasibility assessment obtained from the material validation questionnaire obtained 71% included in the interpretation criteria of the "Good" score. Meanwhile, media validation obtained 80% included in the interpretation criterion "Good". The results of the Basuka media effectiveness assessment developed were obtained from the results of student test question sheet data and main field tests.